2017
DOI: 10.3389/fnmol.2017.00261
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Microglia and Macrophage Polarization via Apoptosis Signal-Regulating Kinase 1 Silencing after Ischemic/Hypoxic Injury

Abstract: Inflammation is implicated in ischemic stroke and is involved in abnormal homeostasis. Activation of the immune system leads to breakdown of the blood–brain barrier and, thereby, infiltration of immune cells into the brain. Upon cerebral ischemia, infiltrated macrophages and microglia (resident CNS immune cell) are activated, change their phenotype to M1 or M2 based on the microenvironment, migrate toward damaged tissue, and are involved in repair or damage. Those of M1 phenotype release pro-inflammatory media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…BA (10 μM) alone treatment did not induce any morphological changes of BV-2 cells. Following treatment with LPS, the microglia became fewer and shorter branches with a greatly enlarged cell body, the characteristic shapes of activated microglia ( Cheon et al, 2017 ). However, treatment with BA attenuated the LPS-induced morphological changes in BV-2 microglia.…”
Section: Resultsmentioning
confidence: 99%
“…BA (10 μM) alone treatment did not induce any morphological changes of BV-2 cells. Following treatment with LPS, the microglia became fewer and shorter branches with a greatly enlarged cell body, the characteristic shapes of activated microglia ( Cheon et al, 2017 ). However, treatment with BA attenuated the LPS-induced morphological changes in BV-2 microglia.…”
Section: Resultsmentioning
confidence: 99%
“…ROS have an important role in regulation of signal transduction pathways and gene expression. The role of ROS is critical for reprogramming of macrophage polarization to M2 phenotype, which releases anti-inflammatory mediators related to tissue recovery (Zhang et al, 2013;Cheon et al, 2017). This mechanism is in line with previous reports which have shown that in a spinal cord injury rat model, 810 nm PBMT altered the macrophage/microglia polarization state to a M2 phenotype and elevated expression of anti-inflammatory cytokines such as interleukin (IL)-4 and IL-13 (Song et al, 2017), but suppressed pro-inflammatory IL-6 (Byrnes et al, 2005) resulting in alternative activation of macrophages.…”
Section: Intranasal Photobiomodulation Therapy From the Nostrilsmentioning
confidence: 99%
“…Since delayed treatment of PJ34 was found to suppress neuro-inflammation in the ischemic brain, we further explored whether delayed PARP-1 inhibition could block the activation of microglia or astrocytes. Microglial and astrocytic activation were evaluated as described previously (Cheon et al, 2017;Jiang et al, 2017). CD11b and Iba-1 were used as microglial activation markers, and GFAP was used to assess the activation level of astrocytes.…”
Section: Parp-1 Inhibition Modulates Microglial Activation After Cerementioning
confidence: 99%